Bilingualism as an Effort to Understand Kitab Kuning in Darussalam Boarding School - Elen Inderasari; Dwi Kurniasih (TRANSFORMATIKA, 2018)
This study aims to explore the defense of Java language and bilingualism on the learning process of yellow book in Pondok Pesantren Mahasiswa Darussalam. The data in this study was obtained when asatidz read, interpret, and explain the contents of the yellow book to the students. The method used in this research is descriptive qualitative. Descriptive method is a research method that tries to describe and interpret the object in accordance with the actual situation. This research also uses direct observation method in collecting data in yellow book study at Pondok Pesantren Mahasiswa Darusalam Pucangan Kartasura. The results of this study indicate the existence of the phenomenon bilingualism in the process of learning yellow book. In addition, in this study also shows the occurrence of Java language retention process that can be classified into several forms of words (terms). There are several factors that lie behind the defense of Javanese language and bilingualism that occurred in Pondok Pesantren Mahasiswa Darussalam.